2008
DOI: 10.1111/j.1442-9993.2001.tb00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Paddock-scale patterns of seed production and dispersal in the invasive shrub Acacia nilotica (Mimosaceae) in northern Australian rangelands

Abstract: Paddock‐scale Acacia nilotica L. Willd. ex Del. (prickly acacia) spatial distribution, seed production and dispersal patterns were investigated in the Astrebla (Mitchell) grasslands of northern Australia as a step toward predicting future patterns of invasion. A number of hypotheses were tested based on what we know of this species in both Australia and regions where it is native, for example South Africa. It was hypothesized that most A. nilotica seeds would be produced by trees in riparian habitats with acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Seed production following a dry year in B. retama was similar to the seed production of other woody perennials from more mesic ecosystems (Radford et al, 2001;van Klinken, 2005). It has been suggested that the seed production of most shrubs and trees, including B. retama, in deserts is highly dependent on rainfall (Debandi et al, 2002;Radford et al, 2001;Solbrig and Yang, 1977).…”
Section: Discussionmentioning
confidence: 94%
“…Seed production following a dry year in B. retama was similar to the seed production of other woody perennials from more mesic ecosystems (Radford et al, 2001;van Klinken, 2005). It has been suggested that the seed production of most shrubs and trees, including B. retama, in deserts is highly dependent on rainfall (Debandi et al, 2002;Radford et al, 2001;Solbrig and Yang, 1977).…”
Section: Discussionmentioning
confidence: 94%
“…Other researchers have investigated the potential for cattle to disperse seeds (Carpinelli et al, 2005;Cosyns et al, 2005a, b;Doucette et al, 2001;Gardener et al, 1993;Ocumpaugh et al, 1996;Radford et al, 2001; Traba et al, 2003); however, few studies have investigated the ability of native ungulates (elk and deer) to disperse viable seeds (Malo and Sua´rez, 1998;Malo et al, 2000;Milton and Dean, 2001;Myers et al, 2004;Vellend, 2002). We projected that native ungulates are also capable of dispersing large quantities of seeds (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Since that time, most research on the topic of seed dispersal has concentrated on fruit and their frugivore consumers and seed dispersers; however, some investigators have pursued this hypothesis. Of the few ecological studies that have studied seed dispersal by ungulates, most have occurred in the old world (Cosyns et al, 2005a, b;Couvreur et al, 2005;Gardener et al, 1993;Malo et al, 2000;Milton and Dean, 2001;Radford et al, 2001;Ramos et al, 2006;Traba et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Regenerating stands of Acacia pendula, particularly morphotypes B and C, appear to be projecting a similar threat onto the threatened grassy woodlands of the Hunter, performing the role of 'ecological engineer' in the terminology of Cuneo & Leishman (2013) as it alters the structural makeup of the vegetation. Similarly, Radford et al (2001) noted that Acacia nilotica, originally introduced from Africa as a stock browse and shade species, has now spread to become a serious weed in parts of the Northern Territory. Reid and Murphy (2008) discuss the implications for herbaria when identification of native Acacias is confused with weedy introduced species which may go un-noticed.…”
Section: Could There Be An Undescribed New Acacia Species In the Hunter?mentioning
confidence: 99%
“…It is not unreasonable to assume, therefore, that once Acacia species had been introduced into the region, their dispersal via livestock across the valley was relatively unregulated. In one study of the introduced Acacia nilotica in the Northern Territory, Radford et al (2001) describe the paddock-scale dispersal of this species by cattle, which readily consume and spread viable seed through their faeces. Paynter et al (2003) reported that the seed of this species take 6 days to move through the gut of cattle, and that 40% of seed passed in this way were viable.…”
Section: Was Acacia Pendula Accidentally Introduced?mentioning
confidence: 99%